Three-Dimensional Filial Piety Scale: Development and Validation of Filial Piety Among Chinese Working Adults - Shi, Juan; Wang, Fengyan (Frontiers in Psychology, 2019)
This study aimed to develop the Three-Dimensional Filial Piety Scale and explore its psychometric properties. Based on Wang’s Three-Dimensional Filial Piety Model, our study employed a review of the current literature, in-depth interviews, and feedback from experts and the target group. An initial 36-item scale using a bipolar Likert 6-point rating scale was developed. Then item analysis and exploratory factor analysis were conducted with sample 1 (n = 617) to explore the dimensions and final items, and a 15-item scale with three factors was obtained. After that, confirmatory factor analysis was conducted to validate the 3-factor structure obtained through exploratory factor analysis with sample 2 (n = 585). Next, we tested criterion-related validity with sample 3 (n = 248) and test-retest reliability with sample 4 (n = 67). The results supported the model on which this scale was based and showed three dimensions of filial piety, namely the balance of interests, good affections, and family role norms. As a valid, reliable scale, the Three-Dimensional Filial Piety Scale can therefore be used in the Chinese context to measure filial piety for people of different genders, ages, and cohabitation situations.